2012
DOI: 10.2478/v10045-012-0018-3
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Rate of Chloridazon in Soil as Influenced by Adjuvants

Abstract: Abstract:The aim of this work was to evaluate the influence of an adjuvant addition on chloridazon degradation rate in soil. The experiment was carried out under controlled laboratory conditions. Chloridazon was applied alone and in a mixture with three different adjuvants: oil, surfactant and multicomponent (used for preemergence application). Chloridazon residue was analysed using gas chromatography with electron capture detector (GC/ECD). Good linearity was found between logarithmic concentration of chlorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Considering adjuvants as inert compromises the validity of some pesticide environmental risk indicators, for instance the Groundwater Ubiquity Score or the Environmental Impact Quotient ( 49 ). It is established that the half-life of pesticide active ingredients in soil is extended by the presence of adjuvants as has been demonstrated for chloridazon ( 50 ). A study investigating the leaching of four pesticide formulations (azoxystrobin, propyzamide, triadimenol, and cyproconazole) through a sandy loam soil found that leaching was greater than was the case with their respective active ingredients alone ( 51 ).…”
Section: Regulatory Guidance Values For Pesticides Can Be Miscalculatmentioning
confidence: 99%
“…Considering adjuvants as inert compromises the validity of some pesticide environmental risk indicators, for instance the Groundwater Ubiquity Score or the Environmental Impact Quotient ( 49 ). It is established that the half-life of pesticide active ingredients in soil is extended by the presence of adjuvants as has been demonstrated for chloridazon ( 50 ). A study investigating the leaching of four pesticide formulations (azoxystrobin, propyzamide, triadimenol, and cyproconazole) through a sandy loam soil found that leaching was greater than was the case with their respective active ingredients alone ( 51 ).…”
Section: Regulatory Guidance Values For Pesticides Can Be Miscalculatmentioning
confidence: 99%
“…With regards to volatility, cadusafos is the only pesticide among the detected pesticides with high a volatility (119.6 mPa) while the others have a low volatility ranging between 4.0 × 10-07 mPa and 3.9 mPa (University of Hertfordshire, PPDB). Under optimum soil conditions, pesticides with a higher DT50 and a moderate to a high solubility, have the tendency to be absorbed by roots of crops growing in the field and subsequent crops in crop rotations (Doan Ngoc et al 2015;Hwang et al 2015;Kucharski et al 2012). Pesticides with high volatility can be absorbed by the foliar of non-target crops through spray drift and can also be taken up by crop roots under dry soil conditions.…”
Section: Pesticides Residues In Yam Samplesmentioning
confidence: 99%
“…To increase safety of pesticide use and minimise their negative effect on the environment, a series of new solutions is being introduced, the dominant being the use of adjuvants (Foster et al 2006, Kucharski and Sadowski 2009, Green and Beestman 2007, Kucharski et al 2012, ionic liquids (Pernak et al 2011, Pernak et al 2015 and innovative controlled release formulations. The key objective in the use of such formulations in agriculture is the gradual (controlled) release of the active substance to the environment and, at the same time, minimizing the applied dose (Mogul et al 1996, Flores-Céspedes et al 2007, Fernández-Pérez et al 2011.…”
Section: Włodarczyk and Siwek 2016)mentioning
confidence: 99%